Cervical Disc Degeneration and Vertebral Endplate Defects After the Fused Operation. Issue 18 (15th September 2021) - Leonova, Olga; Baykov, Evgenii; Sanginov, Abdugafur; Krutko, Aleksandr
Abstract : Study Design: Longitudinal study of cervical MR in patients with degenerative disc disease (DDD). Objective: To evaluate the evolution of the degenerative changes in the C2-D1 cervical segments and to assess the association magnetic resonance imaging (MRI) parameters with clinical symptoms after surgical treatment in patients with DDD. Summary of Background Data: The evolution of degenerative changes in the cervical spine is poorly understood. Endplate defects can be of great importance in progressive disc degeneration (DD). Clarification of this predictor may be important in determining the treatment tactics in patients with DDD. Methods: The study included patients who had 2-years' follow-up after cervical fusion for spondylotic radiculo- with/without myelopathy. Demographic data (age, sex, surgical data) were assessed; clinical data (visual analogue scale [VAS] neck, VAS arm, Neck Disability Index [NDI]) and cervical MRI (DD grades by Pfirrmann, Modic changes (MC), total endplate scores (TEPS) were compared to preoperative data. Results: The median follow-up term was 26.5 (18.9–33.1) months. All patients reported a decrease neck pain and arm pain at follow-up ( P < 0.001). There was observed the change in MC types ( P < 0.001) and an increase of TEPS ( P < 0.05). 71.7% discs remained unchanged during the follow-up, but a significant number of discs went from Grade 2 to Grade 3 and from Grade 3 to Grade 4 by Pfirrmann ( P < 0.001). Clinical scores (VAS neck, VAS arm, NDI) had no correlation with MRI changes ( P > 0.05). DD was associated with TEPS (odds ratio [OR] 2.05–5.47, P < 0.05) and patients' age (OR 1.11–2.33, P < 0.05) at all cervical levels; with MC types, but only at C4-C5 and C6-C7 levels (OR = 2.91 and 2.79, respectively, P < 0.05). Receiver-operating characteristic analysis showed a TEPS threshold value of 7, above which the probability of DD significantly higher. Conclusion: During 2 years' follow-up the significant increase of DD grades by Pfirrmann was observed at C4-C6 levels ( P < 0.001). A significant association DD with TEPS and age at all cervical levels was determined. Level of Evidence: 3 Abstract : Longitudinal study of cervical spine degeneration by magnetic resonance imaging in patients after fused operation. During 2 years, the significant increase of disc degeneration grades was observed at C4-C6 levels. No correlation was found between clinical symptoms and disc degeneration. Strong association disc degeneration with endplate defects and age at all cervical levels was determined.